ZIKA Virus Disease as Public Health Emergency and Ethics - Chakraborty, Rhyddhi; Fernandes, Edmond (Bangladesh Journal of Bioethics, 2017)
This paper argues that Zika virus infection has its ethical implications beyond the reproductive health of women. It claims that Zika virus infection like public health emergency exposes the underlying health determinants and health status of women. Therefore, ethical mitigation of Zika like public health emergencies should consider these underlying health determinants and health status of women. For, undermining and overlooking these underlying determinants and health status of women, during the public health emergencies, enhance the health inequities. The recent Zika virus infection in Brazil has triggered different ethics consultation and has prompted to outline ethical recommendations. However, the recommendations have either focused on the reproductive health of women or on the core strategies of public health emergency. Considering this as a gap in perspective to prepare for Zika like public health emergencies, this paper argues that it is the underlying holistic health of women, precisely, health capability, which should be given due ethical consideration. Finally, the paper concludes highlighting the fact that focusing on the holistic health of the women during Zika like public health emergencies and beyond can bring in long-term benefits for global health equity.